Changes of antithroglobulin antibody in children with congenital hypothyroidism - Eun Mi Cho; Uk Hyun Kim; Byung Ho Choi; Cheol Woo Ko (Korean Society of Pediatric Endocrinology, 2013)
PurposeIt has been reported that antithroglobulin (anti-TG) antibody is increased in the sera of both children with transient congenital hypothyroidism and their mothers. And transplacental transport of thyroid autoantibody was proposed as the pathogenesis of transient congenital hypothyroidism. However this is not known in nontransient congenital hypothyroidism. This study was done to see changes of anti-TG antibody in children with nontransient congenital hypothyroidism.MethodsStudy patients consisted of 60 patients diagnosed as congenital hypothyroidism in the Department of Pediatrics, Kyungpook National University Children's Hospital, Daegu, Republic of Korea between January 2010 and March 2013. Healthy control were 45 children showing normal thyroid function. Anti-TG antibody and various laboratory tests were analyzed retrospectively, and compared in both children with congenital hypothyroidism and controls.ResultsAnti-TG antibody was significantly higher in children with congenital hypothyroidism compared to healthy controls, 119.4±34.7 U/mL versus 80.6±19.6 U/mL, respectively (P<0.001). There was no significant difference of anti-TG antibody in gender and age.ConclusionWe observed a significant increase of anti-TG antibody in children with nontransient congenital hypothyroidism compared to healthy controls. Further study focusing pathogenetic role of anti-TG antibody in nontransient congenital hypothyroidism is necessary. Furthermore, the clinical significance in the course of congenital hypothyroidism need to be known.